2014
DOI: 10.1080/00224499.2014.894490
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Sexual Five-Facet Mindfulness Questionnaire (FFMQ-S): Validation Among a Community Sample of French-Speaking Women

Abstract: It has been recently demonstrated that mindfulness-based intervention may be particularly suitable for addressing sexual difficulties in women. Although the FiveFacet Mindfulness Questionnaire (FFMQ) is currently one of the most widely used scales to assess mindfulness, no adaptation and validation of the FFMQ to measure female sexual functioning has been published. The main aim of this study was to develop and validate a sexual version of the Five Facets Mindfulness Questionnaire (FFMQ-S) to specifically meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…These findings corroborate well established theories of sexuality, which posit that paying attention to here-and-now sensations and reducing tendencies to evaluate or judge one's own or one's partner's performance during sexual activity are important for satisfied, quality sexual experiences with one's romantic partner (Masters & Johnson, 1970). Furthermore, results from the present study complement previous findings of significant correlations between all but the Nonreactivity to Inner Experience facets of mindfulness and sexual functioning (Adam et al, 2014), lending further support to the notion that the five facets of mindfulness may differentially contribute to the sexual and relationship functioning of romantic partners.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings corroborate well established theories of sexuality, which posit that paying attention to here-and-now sensations and reducing tendencies to evaluate or judge one's own or one's partner's performance during sexual activity are important for satisfied, quality sexual experiences with one's romantic partner (Masters & Johnson, 1970). Furthermore, results from the present study complement previous findings of significant correlations between all but the Nonreactivity to Inner Experience facets of mindfulness and sexual functioning (Adam et al, 2014), lending further support to the notion that the five facets of mindfulness may differentially contribute to the sexual and relationship functioning of romantic partners.…”
Section: Discussionsupporting
confidence: 87%
“…However, only one previous study has used Baer and colleagues' five-factor measure to assess links between mindfulness and sexual functioning. In this study, scores on the Observing of Experience, Describing with Words, Acting with Awareness, and Nonjudging of Inner Experience facets of mindfulness, as well as overall level of trait mindfulness, were negatively associated with sexual distress in a sample of adult women (Adam, Heeren, Day, & de Sutter, 2014).…”
Section: Mindfulness and Sexual Satisfactionmentioning
confidence: 94%
“…Several versions of the FFMQ have been validated for use in a large number of populations. In addition, it has been validated for use with meditators and nonmeditators and with individuals suffering from a wide range of clinical psychological and medical conditions (Adam, Heeren, Day, & de Sutter, 2014;Barros, Kozasa, Souza, & Ronzani, 2014;Cebolla et al 2012;Christopher, Neuser, Michael, & Baitmangalkar, 2012;de Bruin, Topper, Muskens, Bögels, & Kamphuis, 2012;Deng, Liu, Rodriguez, & Xia, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Brown and Ryan (2003) considered "attention to and awareness of what is occurring in the present" (p. 824) as a central aspect of mindfulness, unlike non-reactivity, non-judgment, or acceptance, which might be outcomes of practicing mindfulness (see Jermann et al, 2009 for a review). Moreover, a recent study (Adam, Heeren, Day, & de Sutter, 2014) has shown significant negative links between a sexual mindfulness scale and sexual distress among women. In particular, the study revealed that the facets describing (e.g.,"I easily feel my emotions during sexual intercourse") and acting with awareness (e.g., "I usually feel quite available and present during sexual intercourse") were significantly more related to the absence of sexual distress than the other facets of the scale (observing, non-judging of inner experience and non-reactivity to inner experience).…”
Section: Mindfulnessmentioning
confidence: 99%